Music therapy for improving premature infants' well-being and communication skills and enhancing mother-infant bonding : a case study - Antonakopoulou, Stefania (2016)
Over the last few decades, mother-child attachment has received increasing attention in early intervention with prematurely born infants. In these early years, physical interactions constitute a crucial arena for early learning and brain development, and together with the strong emotional bonding between the mother and her infant, they build the foundation for later interaction relationships. Premature birth is a challenging experience for the mother-infant relationship and is always a risk factor in early interaction issues (long hospital stay, lack of physical closeness etc.). This case study aims to examine how music therapy can promote premature infant's well-being and encourage the creation of a healthy mother-infant bonding. The current investigation involved the observation and qualitative analysis of twelve recorded video data of mother-infant music therapy sessions and an in-depth, semi-structured interview with the music therapist analyzed with Interpretative Phenomenological Analysis. Findings of the case study included improvement of infant's visual attention abilities, auditory information processing and quality of sleep, as well as important enhancement of mother-infant relationship with the participation in music therapy activities. Along with former studies on effective music therapy for preterm infants, these findings show the power of music therapy on infant's physical and psychological state, as well as on the rapprochement of this valuable mother-infant bond at this early stage. Further research could be conducted on the creation of greater and effective music therapy techniques for premature infants during and after leaving the hospital, which would encourage all parents to work the relationship with their baby.